Historical Planktothrix diversity across seven Norwegian lakes implies environmentally driven niche differentiation - Kyle, Marcia; Andersen, Tom; Haande, Sigrid; Rohrlack, Thomas (Frontiers in Ecology and Evolution, 2015)
Non-ribosomal synthetase-produced cyanopeptoline oligopeptides enables differentiation of subpopulations of the cyanobacterial genus Planktothrix into chemotypes. It is unknown what influences the population structuring of these chemotypes. Sediment cores from seven lakes in southern Norway allowed temporal reconstruction of chemotype diversity from sites where there is only fragmented historical information. Sediment DNA was amplified using primers designed to specify the chemotype variations found within the cyanopeptoline ociB gene cluster. Findings indicate that of the seven lakes studied, only two lakes had Planktothrix populations containing all four of the most common Norwegian chemotypes. We used principal component analysis and Kendall tau analysis to investigate the ability of monitoring data to predict chemotype diversity, and to identify possible biotic or abiotic barriers to chemotype dispersal. The best predictor was a negative relationship between number of chemotypes present in a lake and the concentration of chlorophyll a in the top 0–4 m. At low chlorophyll a concentrations, light penetration is typically deeper, which could allow light tolerant Planktothrix to move deeper into the colder waters. Recent research findings have suggested this allows for a window of opportunity for Planktothrix to escape parasitism. With this added cold, light-constrained niche, more chemotypes might find refuge. The resulting increase in chemotype diversity within Planktothrix populations could present a greater defense against parasitism when conditions varied, such as by seasonal light changes.